The COVID-19 outbreak and corporate cash-holding levels: Evidence from China - Zhou, Donghua; Zhou, Hua; Bai, Min; Qin, Yafeng (Frontiers in Psychology, 2022)
By employing data from Shanghai and Shenzhen A-share markets for the period of 2019-2020, this paper examines the relationship between the degree of the COVID-19 pandemic's impact on firms’ cash-holdings levels in China. We find that firms that are severely affected by the COVID-19 pandemic have higher current cash holdings levels, suggesting that the more positive (negative) the management tone in responding to the COVID-19 pandemic impact, the lower (higher) the firm’s current cash holdings. However, future corporate cash holdings decrease considerably irrespective of the corporate sentiment towards COVID-19. The positive sentiment of each firm’s management team towards the supply chain and the government policies results in a relative reduction of current cash holdings, whereas the severe impact on operating performance, especially the impact of the outbreak on the supply chain, demand, production and operations, and government policies, reduces the firm’ s future cash holdings. In addition, the impact of the pandemic has increased the current cash holdings of state-owned enterprises and reduced the future cash holdings of non-state-owned enterprises. Meanwhile, companies located in a city with a higher density of population or companies that experience relatively higher competition in the industry tend to undergo a severer impact on their current and future cash holdings due to the COVID-19 pandemic. Overall, this study sheds the light on stimulating the vitality of enterprise investment and promoting the domestic economic cycle.